2019
DOI: 10.5296/jbls.v2i1.535
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis in Febrile Patients: Diagnosis by Serology and Polymerase Chain Reaction

Abstract: Introduction: Leptospirosis is a zoonotic disease found in all tropical and temperate areas of the world. Humans contract leptospira through mucosal or percutaneous exposure to environments contaminated by the urine of chronically infected animal sources mainly rodents, dogs, pigs and cattle.Objectives: It is known that IgM ELISA is used widely to diagnose leptospirosis in acute stage of illness.Our aim is to evaluate the sensitivity and specificity of a molecular technique like PCR in reference to the serolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, we confirmed only two leptospirosis cases using EMJH culture media throughout Bangladesh for a period of one year. The earlier studies were based on highly sensitive serological tests [ 41 43 ], so our culture-based approach underestimated the contribution of Leptospira to the burden of febrile illness in these hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…However, we confirmed only two leptospirosis cases using EMJH culture media throughout Bangladesh for a period of one year. The earlier studies were based on highly sensitive serological tests [ 41 43 ], so our culture-based approach underestimated the contribution of Leptospira to the burden of febrile illness in these hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Perwez et al reported that PCR was superior in the first week of illness to ELISA IgM, Figure 2. Geographical distribution of cases included in this study but a low positivity was observed from the 8th day, and during 13 -15 days, ELISA IgM was superior to PCR (24).…”
Section: Discussionmentioning
confidence: 68%
“…The positivity of SAT and ELISA IgM for all 67 sera was 48 (71.6%) and 39 (58.2%), respectively. In the case of the unavailability of the reference serology test (MAT), ELISA IgM and SAT can detect leptospirosis at the acute and convalescent stages, with high sensitivity as reported (2,4,19,23,24). Therefore, we suggest that patients who had negative results by ELISA IgM and SAT might have not leptospirosis.…”
Section: Discussionmentioning
confidence: 79%